TECHNOLOGIES FOR DEVELOPING THE CREATIVE ABILITIES OF OLDER PRESCHOOL CHILDREN: AN INNOVATIVE APPROACH AND PEDAGOGICAL OPPORTUNITIES - Urmonova T. I. (Bright Mind Publishing, 2026)
This article analyzes the peculiarities of creative abilities of preschool children, the principles, directions and technologies of their development. Also, the possibilities for the development of creative abilities and creativity in children are commented on by the application of Quest game technology
Keywords: Preschool age, creative abilities, creativity, Quest Game Technology, principles, directions, quest assignments, spiritualization.